Effect of phyllosphere and spike mycoflora on castor gray mold incited by Amphobotrys ricini: EFFECT OF MYCOFLORA ON CASTOR GRAY MOLD - C YAMUNA,; P KISHORE VARMA,; R D PRASAD,; K VIJAYA LAKSHMI, (Journal of Oilseeds Research, 2015)
Gray mold of castor incited by Amphobotrys ricini is an economically important disease causing heavy losses during capsule formation stage under high humid conditions. The phyllosphere and spike mycoflora were isolated from castor and tested for their bioefficacy against gray mold under laboratory and greenhouse conditions. The mycoflora isolated were identified based on morphological characters as species of Acremonium, Aspergillus, Choanephora, Cladosporium, Fusarium, Macrophomina and Penicillium. Among the mycoflora tested in vitro, highest inhibition of the test pathogen was recorded with Acremonium species. Greenhouse evaluation of phyllosphere and spike mycoflora by detached spike method has shown that inoculation of detached spikes with Penicillium spp. 24 hours prior to pathogen inoculation has significantly reduced gray mold severity compared to control.